Influence of Nickel and Aluminum in Bentonite for Ethanol-to-Gasoline Reaction - Robert Ronal Widjaya; Yusraini D. I. Siregar; Syifa H. Nabillah; Nino Rinaldi; Sabar P. Simanungkalit; Joni Prasetyo; Adid Adep Dwiatmoko (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Bentonite can be used as a catalyst due to its flexible structure. However, it has several drawbacks, including low thermal and hydrothermal stability, as well as a small surface area and pore volume. This study aims to modify the structure of bentonite using the pillared clay (PILC) method, in order to improve its physicochemical properties and catalytic activity. The bentonite was pillared with aluminium (Al/PILC), nickel (Ni/PILC), and a combination of both metals (Al-Ni/PILC). Catalyst characterization was carried out using X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), Surface Area Analyzer (SAA), Fourier Transform Infrared Spectroscopy (FTIR), Temperature Programmed Desorption of Ammonia (TPD-NH₃), Thermogravimetric Analysis-Differential Scanning Calorimetry (TGA-DSC), and Gas Chromatography with Flame Ionization Detection (GC-FID). XRD analysis showed an increase in the interlayer spacing, the largest basal spacing is observed in Al/PILC. XRF results indicated an increase in the composition of Al₂O₃ and NiO in all four catalysts. SAA analysis demonstrated an increase in surface area and pore volume across the catalysts, the highest surface area is exhibited by Al/PILC (187.83 m2/g), while the largest pore diameter is observed in Al-Ni/PILC (12.83 nm). The acidity analysis using TPD-NH₃ shows that Al/PILC possesses the highest acidity value of 2.34 mmol/g. The presence of Brønsted acid sites was confirmed through FTIR analysis. TGA-DSC analysis indicated an improvement in the thermal stability of all tested catalysts. The Al/PILC catalyst showed the best performance at 150 °C. When the reaction temperature was increased to 250 °C, the Al-Ni/PILC catalyst demonstrated the highest efficiency in the ethanol-to-gasoline conversion process. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).